Mama - Hopkins, Lee Bennett; Marchesi, Stephen (New York : Simon & Schuster Books for Young Readers, 1992)
A young boy describes his mother's struggles to feed, clothe, and protect him and his little brother using whatever resources she can muster, including stealing.
Keywords: Single-parent families -- Fiction; Stealing -- Fiction; Mothers and sons -- Fiction; Brothers -- Fiction; City and town life -- Fiction